Low Iodine Status in a Large Pregnancy Cohort in Ireland - Lisa Kelliher; Mairead Kiely; Jillian Brown; Yvonne O’Callaghan; Áine Hennessy (Proceedings)
Background: Iodine is an essential component of the thyroid hormones thyroxine (T4) and triiodothyronine (T3), which are required for brain development [...]